Uncertainty and Surprise in Complex Systems Questions on Working with the Unexpected - McDaniel, Reuben R.; Driebe, Dean J. (Understanding Complex Systems,, 2005)
Complexity science has been a source of new insight in physical and social systems and has demonstrated that unpredictability and surprise are fundamental aspects of the world around us. This book is the outcome of a discussion meeting of leading scholars and critical thinkers with expertise in complex systems sciences and leaders from a variety of organizations sponsored by the Prigogine Center at The University of Texas at Austin and the Plexus Institute to explore strategies for understanding uncertainty and surprise. Besides distributions to the conference it includes a key digest by the editors as well as a commentary by the late nobel laureat Ilya Prigogine, "Surprises in half of a century". The book is intended for researchers and scientists in complexity science as well as for a broad interdisciplinary audience of both practitioners and scholars. It will well serve those interested in the research issues and in the application of complexity science to physical and social systems.